The issue of recreational use of sildenafil - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Justyna Drogoń; Weronika Chachaj; Paulina Słomka; Edyta Gwóźdź; Dawid Konieczko; Ewa Gardocka (Kazimierz Wielki University, 2024)
Introduction and purpose Erectile dysfunction (ED) is defined as the inability to achieve and maintain an erection sufficient for satisfactory sexual intercourse. Sildenafil is one of the most popular medications used to treat ED, but in recent years, there has been a growing trend of recreational use of this drug, particularly among younger individuals, which can lead to numerous negative health consequences. The aim of this article is to provide an overview of the recreational use of sildenafil, especially among younger individuals. State of knowledge Sildenafil primarily affects the smooth muscle of the blood vessels in the corpora cavernosa, facilitating the achievement and maintenance of an erection. The most common side effects of sildenafil include headaches, dizziness, facial flushing, nausea, muscle pain, and nasal congestion. A relatively rare but potentially severe side effect of sildenafil is priapism. It is noted that those using sildenafil recreationally often have multiple sexual partners, as the drug helps them prolong sexual encounters. Studies show that sildenafil is used by groups that should have no problem achieving sexual satisfaction. The use of the drug in combination with alcohol and other substances is noticeable. Conclusions Recreational use of sildenafil appears to be an increasingly common behavior among young men who do not have difficulties achieving or maintaining an erection. There are no studies yet that specifically examine the recreational use of sildenafil among women. It is necessary to conduct further research to better understand the prevalence of this phenomenon and to identify the factors that predispose individuals to engage in recreational use of sildenafil.